An engineering-geological study of rock soils and the products of their fracture zones (Albazinskoe deposit, north Khabarovsk Krai) - T. G. Ryashchenko; E. A. Maslov; E. V. Bryzhak; S. I. Shtel’makh (Известия высших учебных заведений: Геология и разведка)
Background. The results of an engineering-geological study of rock soils and the products of their fault zones are considered on the example of samples selected in the sides of the Albazinskoe gold-bearing deposit located in the north of the Khabarovsk Krai.Aim. To develop and implement a methodological approach, which includes laboratory determinations of the velocity of propagation of longitudinal seismic waves (“seismic speed”) using a “Pulsar-2.2” unit (methods of continuous and through sounding), as well as density, porosity and water absorption determinations along with obtaining information about the types of microstructure and microtexture, the mineral composition and mineral alteration features under the influence of metamorphism (using petrographical thin sections).Materials and methods. For the collected rock soil samples the relationship between seismic velocity and physical properties indicators was evaluated (R-type cluster analysis programme). The products of fractural zones were studied in a laboratory according to a specially-developed methodological approach: extended (black clay) and reduced (crushed stone formations with debris). The microelement composition of the clay and gravel of argillites was determined for the first time, and the level of their pollution by toxic microelements (Zc index) was evaluated.Results. On the basis of quantitative assessment of the relationship between indicators of rocky soils various properties identified using the cluster analysis program, an “anomalous” conclusion is obtained about the absence of the rock soil density effect on seismic properties, which can be explained by the textural and structural features, as well as by mineral composition and the consequences of metamorphism (cataclastic and blastogenetic features recorded on the microscale in thin sections).Conclusion. The proposed methodological approach can be recommended for further studies of seismic, strength and physical properties of rocky soils during seismological and engineering-seismological studies of various territories.